Evaluation of the Energy Impact of Green Area Surfaces and Vegetation Cover in Forested Urban Environments with Dry Climates. Case: Mendoza Metropolitan Area, Argentina - Arboit, Mariela Edith (2017)
The object of this work is to study the energy impact caused by green surface area and vegetation coverage present in the low-density urban environment in the metropolitan area of Mendoza (AMM), Argentina, in order to understand the morphology of forested city in an arid climate, and, in the future, to determine the potential real modification on those urban microclimate environments essentially dependent on energy exchanges.Methogically on the urban green space level, the green surface and the different mineralized surfaces have been quantified from surveyed land data, aerial photographs, and by an accompanying representative in-situ survey of 32 city blocks in the AMM. In addition, using the i-tree canopy tool, the urban area covered by tree vegetation mass or vegetation cover has been quantified. Subsequently, using ecophysiological coefficients1, an environmental index for each environment analyzed has been determined, indicating the percentage of the total area of green space environmentally useful as an environmental modifier.The results obtained indicate mean values of green surface (herbaceous grass) of 22.83% in the urban environments analyzed (20.22% public and private), plus a 2.62% non-mineralized surface devoid of vegetation cover (permeable irrigation channel). The results using the i-tree tool indicate an urban surface covered by a vegetation tree mass of 26.59%, and a total of 41.08% non-mineralized surface, including trees, grass lawns, bushes and bare ground. In terms of environmental indices, values were established for the 32 environments analyzed, from a mean of 0.46, with the highest indices of 0.59 through the positive effect of vegetation cover from the thermodynamic point of view, and, on the other hand, with minimum indices of 0.39 in environments with a low percentage of urban trees and a high quantity of mineralized surface directly exposed to solar radiation.As a result of such a process, it is possible to determine current conditions and the formulation of an environmental diagnosis based on vegetation cover, adapted to consolidated environments of low density in a model of a forested city in arid climate, and it is hoped that this work presents the possibility of evaluating the energy impact of vegetation cover to implement future norms and rules aimed both at preserving the forested city model, in equilibrium with a model of the sustainable city, and at reversing urban-building growth that does not take such factual indicators into consideration.